The best little whorehouse in Texas [videorecording (Blu-Ray)] - Higgins, Colin, 1941-1988; Reynolds, Burt; Parton, Dolly; DeLuise, Dom (KL studio classics., 2025)
The Best Little Whorehouse in Texas documents in rousing song and dance, a new Texas legend, which now joins the Alamo as a historical institution, immortalized in story, song, book, play and movie. The demise of the real-life Chicken Ranch inspired the hit stage musical, and now this boisterous big-screen adaptation headed by superstar Burt Reynolds as Sheriff Ed Earl Dodd and red-hot country legend Dolly Parton as the Chicken Ranch's proprietress, Miss Mona. The two join together not only in romance, but to fight big-city TV crusader Melvin P. Thorpe in his efforts to expose the Chicken Ranch to public scandal, and thus close it down.